Benzothiazinone-piperazine derivatives as efficient Mycobacterium tuberculosis DNA gyrase inhibitors. Issue 2 (June 2015) - Chandran, Manoj; Renuka, Janupally; Sridevi, Jonnalagadda Padma; Pedgaonkar, Ganesh S.; Asmitha, Vanaparthi; Yogeeswari, Perumal; Sriram, Dharmarajan
Abstract Background and objectives Bacterial DNA topoisomerases are unique in maintaining the DNA topology for cell viability. Mycobacterium tuberculosis (MTB) DNA gyrase, a sole type II topoisomerase has a larger scope as a target for developing novel therapeutics. In this study, an effort was made towards the design and synthesis of benzothiazinone-piperazine hybrid analogues to obtain the possibility of it to lead development through the molecular hybridization technique. Methods A five-step scheme was followed to obtain a series of 36 benzothiazinone-piperazine derivatives and to evaluate them for MTB DNA gyrase inhibition, antimycobacterial and cytotoxicity studies. Results Compound N-(4-chlorophenyl)-4-(6-nitro-4-oxo-4H-benzo[e][1, 3]thiazin-2-yl)piperazine-1-carbothioamide (18) showed greater inhibitory potential with an IC50 of 0.51 ± 0.16 μM in the DNA supercoiling assay of MTB with a moderate anti-tubercular activity of 4.41 μM. The compound even passed the safety profile of eukaryotic cell cytotoxicity with a 1.81% inhibition in the RAW 264.7 cell line at 100 μM concentration. Conclusions This study describes the discovery of benzothiazinone as gyrase inhibitors with potent MTB MIC and inhibitory profiles of the gyrase enzyme with less cytotoxic effect. Furthermore, it is believed that this class of compounds has the potential to be further developed as an anti-TB drug candidate.